2019
DOI: 10.3390/su11020414
|View full text |Cite
|
Sign up to set email alerts
|

Supercapacitor Energy Storage Device Using Biowastes: A Sustainable Approach to Green Energy

Abstract: The demand for renewable energy sources worldwide has gained tremendous research attention over the past decades. Technologies such as wind and solar have been widely researched and reported in the literature. However, economical use of these technologies has not been widespread due partly to cost and the inability for service during of-source periods. To make these technologies more competitive, research into energy storage systems has intensified over the last few decades. The idea is to devise an energy sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
112
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 229 publications
(115 citation statements)
references
References 189 publications
1
112
0
2
Order By: Relevance
“…Phosphorous and nitrogen co-doped activated carbon from spent coffee grounds was synthesized using ammonium polyphosphate via microwave-assisted synthesis [10]. In our previous studies, we have reported facile production of bio-waste-derived activated carbons using KOH activation, for supercapacitor applications [11][12][13][14][15][16]. Utilizing the KOH activation technique, we have demonstrated varied pore size distribution, control over the surface area of activated carbons and a resulting promising charge storage performance of the device.…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorous and nitrogen co-doped activated carbon from spent coffee grounds was synthesized using ammonium polyphosphate via microwave-assisted synthesis [10]. In our previous studies, we have reported facile production of bio-waste-derived activated carbons using KOH activation, for supercapacitor applications [11][12][13][14][15][16]. Utilizing the KOH activation technique, we have demonstrated varied pore size distribution, control over the surface area of activated carbons and a resulting promising charge storage performance of the device.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the application of CEA could reduce the installed power of power units within an energy supply system (transformers, converters, junction substations, etc.). In this case, the need to implement the onboard CEA in subway has been substantiated in numerous papers both by domestic and foreign researchers [2,3,[6][7][8]. Analysis of above studies has made it possible to establish that one of the essential, yet insufficiently investigated, issues related to the implementation of onboard CEA in the subway has been the choice of their rational parameters, first of all, power and energy intensity.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Among the devices used as electrical energy storage systems, supercapacitors are the devices between conventional capacitors and rechargeable batteries and have found wide applications in aircrafts (Airbus 380), consumer electronics, emergency backup powers, and hybrid or electric vehicles [ 1 ]. Based on the energy storage mechanism, supercapacitors can be classified as EDLCs, pseudocapacitors, and hybrid supercapacitors composed of an EDLC and a pseudocapacitor [ 1 ]. Due to the sluggish reaction kinetics of metal oxides, the major electrode materials, pseudocapacitors have poor cycle stability compared to EDLCs.…”
Section: Introductionmentioning
confidence: 99%